To protect and serve while protecting privileges and serving male interests: hegemonic masculinity and the sense of entitlement within the Icelandic police force - Steinþórsdóttir, Finnborg S. (Policing and society, 2022)
The police force and police work are gendered and male dominated. Progression towards gender equality is slow despite multiple efforts to enable change. Greater attention is needed regarding men’s perspectives on gender equality, including the preconceptions and prejudices that sustain this hegemonic masculine culture. Drawing on a survey of the whole population of the Icelandic police force, we find gender differences in attitudes towards gender equality and gendered stereotypes. Men are more likely to believe that there are equal opportunities within the police force despite holding negative attitudes regarding women’s ability to serve in the police. Young policemen and those policemen that are not satisfied with their own career progression are more likely to have negative attitudes towards women, although for different reasons, than their older and their more satisfied male colleagues. Applying Connell’s hegemonic masculinities, Silvestri’s exemplar of the ‘ideal’ police officer and Kimmel’s theorisation of male entitlement, we contend that hegemonic masculinity, specifically the exemplar of the ‘ideal’ police officer and police leader, stimulates masculine entitlement. Progress towards gender equality in the workplace poses a threat to entitled men, who may not feel powerful but often believe they deserve to be in power because of the ideology surrounding what it is to be a police officer. Men’s inferior attitudes towards women contribute to the masculine police culture that maintains the gender hierarchy within the the police. The findings reflect the urgent need to take action, specifically against the cultural conceptualizations of police work and the ideal police officer.